Oxidation and Reduction Dual-Responsive Polymeric Prodrug Micelles Co-delivery Precisely Prescribed Paclitaxel and Honokiol for Laryngeal Carcinoma Combination Therapy - Zhou, Lanzhu; Wu, Jun; Sun, Zhe; Wang, Wenzhong (Frontiers in Pharmacology, 2022)
Laryngeal carcinoma is the most common head and neck malignancy in the world. Chemotherapy is still the most common treatment for laryngeal carcinoma. Monotherapy has become powerless due to the lack of drugs in the anticancer agent library, the difficult process of new drug discovery, and the widespread prevalence of drug resistance. Combination therapy with two agents, especially Chinese herbal medicines combined with chemotherapy drugs, is a potential alternative to chemotherapy alone. However, combination therapy faces difficulties in delivering multiple drugs to tumor tissue in a precise ratio. Herein, a cocktail polymeric prodrug micelle (PHPPM) was developed using an oxidation and reduction dual-responsive polymeric paclitaxel (PTX) prodrug and polymeric honokiol (HK) prodrug. Both polymeric prodrugs were obtained by covalently conjugating the drug to dextran via diselenium bonds in. After optimization and characterization, PHPPM with the precise mass ratio of PTX and HK was obtained, enabling ratiometric drug loading, synchronized drug release in response to tumor high-level reactive oxygen species (ROS) and glutathione (GSH) environment, long blood circulation, and high tumor accumulation. This co-delivery system can effectively inhibit laryngeal carcinoma growth in vitro and in vivo. Co-delivery of chemotherapy agents and Chinese herbal medicine with a precise ratio and controlled release of the two drugs at the tumor site provides an effective approach for other laryngeal carcinomas clinical therapy.